DIAGNOSTIC ANALYSIS OF ADVANCED WRITING SKILLS IN 5TH-GRADE STUDENTS IN IMPACTFUL CURRICULUM ERA - Fitriya, Intami Dwi; Sukartiningsih, Wahyu; Hendratno, Hendratno; Istiq'faroh, Nurul (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2025)
The curriculum changes are intended to have a positive impact on the educational system in Indonesia. Through the Merdeka curriculum, learning focuses on the main materials, character development, and students' skills. One of the skills that requires creativity and high-level thinking skills is writing. Advanced writing skill aims to enable students to express their ideas and feelings in written form systematically and develop their creative ideas more broadly, clearly, and integratively. Various types of text are studied at elementary school by considering linguistic rules. This study aims to 1) analyze advanced writing skills of 5th-grade students, and 2) analyze difficulties faced by 5th-grade students in advanced writing. The research method used a descriptive qualitative approach to analyze students' advanced writing skills. Subjects in this study were 5th-grade students and teachers in Gresik Regency. Moreover, the data collection techniques were tests and interviews. The results of the study showed that 5th-grade students are able to write essays or writings. However, aspects that must be considered include linguistic rules (spelling, sentence structure, capitalization, and punctuation), diction, coherence between sentences, and abilities in developing ideas or concepts based on something that has not been experienced before. It can be concluded that 5th-grade students have writing skills, but writing procedures and linguistic rules still require greater attention, which must be followed up in line with curriculum changes that are adaptive and relevant to current developments.